Éclairage sur le rôle des moines chartreux du Val-Saint-Esprit dans le démantèlement du château comtal de Gosnay (comté d’Artois, Pas-de-Calais) au début du xvie siècle - Mathieu Béghin (Bulletin du Centre d’Études Médiévales d’Auxerre)
Within the framework of an interdisciplinary research concerning the Carthusian monastery of Val-Saint-Esprit located in Gosnay, we’ve been able to provide a perspective concerning the role the Carthusian monks played in the dismantling of the comtal castle of Gosnay in 1518. Historiography having mainly covered the destructions led by princes as sentences, or to a smaller extent as a preventive policy for territorial defense, this case is unusual as the dismantling is a private action whose purpose is to defend the access to a monastery. The various stages of this process, from the downgrading of the fortified place by the count of Artois, to the various actors of the dismantling and the building materials resale, have been found in administrative, accounting and notarial unpublished information sources, from ecclesiastical and secular spheres.